2015
DOI: 10.1007/s00270-015-1132-1
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Aortic Occlusion Balloon on Mortality After Endovascular Repair of Ruptured Abdominal Aortic Aneurysms: A Meta-analysis and Meta-regression Analysis

Abstract: This study provides meta-analytical evidence that the use of an AOB in unstable RAAA patients undergoing endovascular repair may improve the results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(13 citation statements)
references
References 53 publications
0
11
0
2
Order By: Relevance
“…Therefore, after final quantitative synthesis, 89 articles were selected, including 28 case reports [11, 2046], 25 case series [10, 4771], and 36 (retrospective) cohort studies [12, 72–105]. Also 8 reviews were identified but not included in calculations, due to concern for double counting of unique cases [5, 13, 14, 106110]. Most studies were deemed to be at high risk of bias.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, after final quantitative synthesis, 89 articles were selected, including 28 case reports [11, 2046], 25 case series [10, 4771], and 36 (retrospective) cohort studies [12, 72–105]. Also 8 reviews were identified but not included in calculations, due to concern for double counting of unique cases [5, 13, 14, 106110]. Most studies were deemed to be at high risk of bias.…”
Section: Resultsmentioning
confidence: 99%
“…Two recent systematic analysis by these investigators have helped to consolidate a disparate evidence base [13, 14]. However, a clear mortality benefit has yet to be demonstrated and consequently, the REBOA concept is still not fully embedded as the standard of care in most hospitals.…”
Section: Introductionmentioning
confidence: 99%
“…However, these procedures take time and tend to be extremely invasive. In recent studies, proximal control using an aortic occlusion balloon has been reported as a useful alternative to these procedures . In the present case, because the aneurysm was isolated and located in the right common iliac artery, we were easily able to use a balloon to achieve proximal control of the infrarenal abdominal aorta.…”
Section: Discussionmentioning
confidence: 73%
“…In recent studies, proximal control using an aortic occlusion balloon has been reported as a useful alternative to these procedures. 17,18 In the present case, because the aneurysm was isolated and located in the right common iliac artery, we were easily able to use a balloon to achieve proximal control of the infrarenal abdominal aorta. This dramatically improved the patient's hemodynamics, and successful completion of endovascular repair saved the patient's life.…”
Section: Discussionmentioning
confidence: 77%
“…Reason. According to a meta-analysis including 39 studies (1277 patients), a supraceliac aortic occlusion balloon improves EVAR results in hemodynamically unstable patients with rAAA [91].…”
Section: Treatment Of the Raaamentioning
confidence: 99%